A compact CPW-fed wideband antenna with circular fractal elements for multiband operations. (28th May 2021) - Dhanasekaran, Dileepan; Somasundaram, Natarajan; Rangasamy, Rajkumar
In this article, a compact flower-shaped CPW-fed antenna is designed for a multiband application. The proposed antenna is created by adding circular fractal elements to edges of the octagon and a slot is created with a similar structure of smaller dimension which is responsible for multiband resonance. The antenna has a compact size of 25 mm × 25 mm, and it exhibits four resonance frequency bands at 2.82 to 6.43 GHz, 7.36 to 8.52 GHz, 11.21 to 12.2 GHz, and 14.05 to 15.83 GHz, respectively. Various antenna characteristics parameters like return loss, VSWR, impedance, radiation pattern, current distribution, substrate material properties are discussed. Antenna design can be used for different applications such as WiMAX (IEEE 802.16), WLAN (IEEE 802.11b, 802.11a/g), INSAT, fixed satellite, ITU band, X-band satellite communication, TV broadcasting, BSS, FSS, and Ku-band.